Image-based sexual abuse: Legislative and policing responses - Huber, Antoinette Raffaela (Criminology & criminal justice, 2025)
Twenty-eight in depth interviews were conducted with victims, stakeholders and criminal justice staff to investigate legislative and policing responses to image-based sexual abuse in England and Wales. The research identifies fundamental failures within these responses and therefore calls for urgent change. Findings indicate that victims face fundamental prosecution barriers due to various limitations within the law as well as police failure to implement victim’s rights and provide a sense of procedural justice. This article therefore makes recommendations for stakeholder-informed legislative and policing reform.